Long-term care in Latin America and the Caribbean? Theory and policy considerations - Martín Caruso Bloeck; Sebastian Galiani; Pablo Ibarrarán (Inter-American Development Bank (IDB), 2017)
This paper discusses theoretical and practical issues related to long-term care (LTC) services in Latin America. Demand for these services will rise as the region undergoes a swift demographic transition from its currently young population to a rapidly aging one, especially since the region's aging cohorts are more prone to experience a decline in their functional and physical abilities than elderly people elsewhere in the world. We argue that private insurance markets are ill-equipped to provide coverage to meet the need for LTC, while the amount of personal savings required to afford self-insurance is prohibitively high. We study how developed economies have dealt with the issue of LTC and pay special attention to the most salient features of their LTC programs. We then direct the discussion to Latin America, where LTC may not be an immediate priority, but governments are likely to encourage the development of LTC programs as demand for them steadily grows. In particular, policymakers are probably going to focus initially on LTC programs for the poor and the vulnerable, for whom LTC affordability is a greater problem. We therefore study how basic elements of policy design affect costeffectiveness of LTC programs by means of a formal model. Our study shows that propoor programs are more cost effective when people have the option to receive cash subsidies, and the availability of in-kind and in-cash choices reduces program costs overall. We argue that our findings are natural starting points to start thinking about LTC program development in the region.
Keywords: J14; N36; 330; long-term care; long-term care insurance; population aging; Latin America